Quality of Life among Haemophilic Children in Central Madhya Pradesh, India: A Cross-sectional Study - Madhuri Tejwani; Pankaj Pal; Gaurav Kumar Prajapati; Vipin Thakur; Shweta Sharma (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Quality of Life (QoL) has recently become a focus of research in haemophilia, as children with haemophilia miss out on opportunities to reach their full potential during school and later in life. This leads to emotional and behavioural problems, family issues, and a decrease in Health-related Quality of Life (HRQoL). There is very limited data from the state of Madhya Pradesh, India, to assess the QoL in haemophilia patients. Aim: To study the clinical profile of haemophilic children and assess their QoL. Materials and Methods: The present hospital-based cross-sectional study was conducted in the Department of Paediatrics, Gandhi Medical College, Bhopal, Madhya Pradesh, India, from January 2019 to December 2019. A total of 49 children (Institutional incidence), aged from 4-12 years, with factor VIII/IX deficiency who presented in the Paediatric ward of the study Institution for factor transfusion, were included in the study. The study population was divided into two groups with children aged (group ) and children aged 8-12 years (group II). A detailed clinical history was obtained from the accompanying parent/guardian, and QoL was measured using the Haemophilia QoL (Haemo-QoL) questionnaire. Scores achieved in each dimension, as well as, the total score were combined on a scale ranging from 0 to 100. High values indicate high impairment in QoL. The meanings of different scales like Standardised and Transformed Scale Scores (TSS) of Haemo-QoL were analysed using the student’s t-test. Results: In the present study, haemophilia A was more common than haemophilia B. All patients who attended the paediatric ward for factor transfusion were males, with a mean age of 8.37±2.56 years. It was also observed that the proportion of patients who were diagnosed early was significantly higher in the 4-7 years age group compared to the 8-12 years age group of patients (p-value<0.05). The present study revealed that the mean overall scores on the Haemo-QoL for the age groups 4-7 years and 8-12 years were 41.92±17.95 and 51.84±16.36, respectively. The highest impairment was in the physical health, school and sports, and family dimensions of QoL. Conclusion: The QoL is poor among children in both age groups. The current study also showed that as age advances, the QoL of haemophilia patients becomes poorer.